Chaotic analysis of heart rate dynamics after an exercise with flexible pole - Antonio, Ana M. S.; Garner, David M.; Raimundo, Rodrigo D.; Abreu, Luiz Carlos De; Navega, Marcelo T.; Valenti, Vitor E. (Mavera Edições Técnicas e Científicas Ltda, 2016)
INTRODUCTION: Exercises with a flexible pole have been applied in clinical practice for upper limb rehabilitation. Nevertheless, its acute effects on cardiac autonomic regulation are unclear.OBJECTIVE: To evaluate the acute effects of exercise with flexible pole on complex behavior of heart rate variability (HRV).METHOD: We investigated 32 healthy female volunteers aged between 18 and 25 years who performed a session of exercise with a flexible pole. HRV was analyzed 10 minutes before and 10 minutes immediately after the exercise.RESULTS: Exercises with a flexible pole did not significantly change time and frequency domain indices of HRV. Non-linear analysis of HRV through the Higuchi Fractal Dimension was not significantly changed during recovery from exercise compared to the control reading at rest.CONCLUSION: Exercises with the flexible pole were unable to acutely change chaotic behavior of heart rate dynamics. This is advantageous for assessments of levels of rehabilitative treatment required in such patients; and their susceptibility to dynamical diseases.

INTRODUÇÃO: Exercícios com uma barra flexível têm sido usados na prática clínica para a reabilitação do membro superior. No entanto, os seus efeitos agudos sobre a regulação autonômica cardíaca não estão bem esclarecidas.OBJETIVO: Avaliar os efeitos agudos do exercício com barra flexível sobre o comportamento complexo da variabilidade da frequência cardíaca (VFC).MÉTODO: Foram investigadas 32 voluntárias saudáveis com idades entre 18 e 25 anos que realizaram uma sessão de exercício com barra flexível. A VFC foi analisada 10 minutos antes e 10 minutos imediatamente depois do exercício.RESULTADOS: Os exercícios com a barra flexível não alteraram significativamente os domínios de tempo e frequência de VFC. Análise não-linear da VFC através da Dimensão Fractal Higuchi mostra que a mesma não foi significativamente alterada durante a recuperação do exercício em relação ao controle pré-exercício.CONCLUSÃO: O exercício com a barra flexível não alterou profundamente o comportamento caótico da dinâmica da frequência cardíaca. Isto é vantajoso para a avaliação de níveis de tratamento de reabilitação necessário em tais pacientes; e sua suscetibilidade a doenças dinâmicas.
ANÁLISE CAÓTICA DA DINÂMICA DA FREQUÊNCIA CARDÍACA APÓS EXERCÍCIO COM BARRA FLEXÍVEL
Keywords: Autonomic Nervous System; Higuchi Fractal Dimension Rehabilitation Medicine; Sistema Nervoso Autônomo; Dimensão Fractal Higuchi; Medicina de Reabilitação